Methane Gas Detection Using IOT - Mohamed Nazimuddin, Mohamed Fahtul Norman; Mohamed Alik, Riyaz Ahmad (Evolution in Electrical and Electronic Engineering, 2023)
Methane gasses are colorless, odorless and flammable gaseous. The methane gas is highly flammable and can lead to a pit fire at the landfill site. In Malaysia, there are numerous landfills that produce a lot of waste. This situation can lead to an increase in methane gas production. A monitoring system will help the worker to avoid a fire at the landfill. The purpose of this project is to detect the methane gas release and monitor the gas in a certain area in order to prevent fire. This project uses using MQ-4 sensor to detect the methane gasses at the landfill site. The system will collect the data from the sensor and store it in the Blynk application to monitor the methane gas in real-time. The results show that the suitable range from the source of the methane gas and the MQ4 gas sensor is within 1 to 2 cm. The test that has been done is to examine the performance and its reliability to ensure the device worked well. In addition, the collected data can be displayed and stored in the Blynk application.